THE ROLE AND SIGNIFICANCE OF ABU AL-BARAKAT AL-NASAFI’S WORK MADARIK AL-TANZIL IN QUR’ANIC EXEGESIS (The Journal of Interdisciplinary Human Studies, 2026)
This article presents a comprehensive scientific analysis of “Madarikal-tanzil wa haqaʼiq al-taʼwil,” a Qurʼanic exegesis authored by Abu al-Barakat alNasafi (d. 710/1310). The research examines the reasons for the composition of thework, its methodological framework, the primary sources employed by the author, andits significance within Sunni theological tradition. In addition, the article explores therelationship between this tafsir and the exegetical works “al-Kashshaf” by Mahmudal-Zamakhshari and “Anwar al-tanzil wa asrar al-taʼwil” by Nasir al-Din al-Baydawi,highlighting their influence on its scholarly and methodological structure. The studyalso provides an overview of manuscript copies of the tafsir, as well as commentariesand marginal glosses written on it, and discusses its place in contemporary academicresearch across Uzbekistan, Türkiye, Saudi Arabia, and Indonesia.
Keywords: Madarik al-Tanzil; Qurʼanic exegesis; Transoxiana; Maturidism; Ahl al-Sunnah wa al-Jamaʼah; manuscripts; commentary; marginal gloss; Islamic source studies.